Planning and assessment for biodiversity conservation at a landscape-scale: an evaluation of current approaches and opportunities in Australia - Pope, Jennifer; Moore, Susan (University of Tasmania, 2013)
The purpose of the report is to analyse the strengths and weaknesses of the range of mechanisms availablefor planning biodiversity conservation at a landscape-scale in Australia. Particular attention was made tostrategic assessment and bioregional planning because of the strong emphasis on both as ‘solutions’ inthe Hawke Review (2009b). The report informs the Landscapes and Policy Research Hub’s development oftools, techniques and policy options to integrate biodiversity into regional scale planning. It is intended as a guide for policy makers on planning and management of biodiversity at a regional scale.